2022
DOI: 10.1111/papt.12412
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in a cognitive rehabilitation programme for people with serious mental illness: A qualitative analysis

Abstract: Objective: Therapeutic alliance is an important element of evidence-based treatments for people diagnosed with a serious mental illness. Cognitive enhancement therapy (CET) is an efficacious cognitive rehabilitation programme that emphasizes coach-participant relationships. The purpose of this study was to examine experiences of therapeutic alliance among CET participants. Design: We used an exploratory qualitative approach. Methods: Semi-structured interviews were conducted with 24 participants diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Regarding similarities between the two groups of clinicians, not surprisingly we found that both groups focused on the therapeutic relationship and monitoring progress. Therapeutic alliance has long been recognized as an important element of recovery-oriented care for persons with psychosis, is associated with recovery outcomes, 11 , 35 , 36 and is recognized by clinicians from qualitative interviews as an important element of psychiatric rehabilitation. 13 , 14 , 23 Although the groups both valued the relationship, they were described differently.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding similarities between the two groups of clinicians, not surprisingly we found that both groups focused on the therapeutic relationship and monitoring progress. Therapeutic alliance has long been recognized as an important element of recovery-oriented care for persons with psychosis, is associated with recovery outcomes, 11 , 35 , 36 and is recognized by clinicians from qualitative interviews as an important element of psychiatric rehabilitation. 13 , 14 , 23 Although the groups both valued the relationship, they were described differently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, video sessions realized new rapport-building opportunities encouraging an equal stance for joint reflection in which therapist and client existed in their personal physical spaces, buttressed by shared interests and common human experiences related to the pandemic. This virtual environment afforded the opportunity for the therapist to build rapport through genuineness and authenticity, an important element of the therapeutic alliance (Faith et al, 2022;Schnellbacher & Leijssen 2009). In the case of George, he declined video sessions, so therapy began over the telephone.…”
Section: Conflict Of Interestmentioning
confidence: 99%